Influence of Cellulolytic Bacteria from Rumen Fluid on in Vitro Gas Production of Fermented Robusta Coffee Pulp (Coffea canephora sp.) - Hanim, Chusnul (2015)
ABSTRACT: The experiment was done to evaluate the influence of robusta coffee pulp fermented by rumen cellulolytic bacteria on in vitro gas production. The first step of this experiment was cellulolytic inoculum production by using fluid fermentation with cellulose as substrat. The inoculum produced was then used for coffee pulp fermentation. Cellulolytic bacteria was added into 200 g coffee pulp as much as 0%, 5% and 10% based on dry matter. Each treatment had three replicates. Fermentation was carried out at room temperature during 21 days anaerobically. At the end of ermentation, samples were taken out for nutrient determination including physical, chemical qualities, and in vitro gas production. Data obtained were analyzed by one way design and continued by Duncan’s new multiple range test to examine the differences between mean values. The results showed that 5% and 10% cellulolytic bacteria addition decreased pH value, and crude fiber (CF) content as much as 12.89% and 16.32% compared to control (0% of cellulolytic bacteria). Whereas addition of 10% inoculum increased nitrogen free extract (NFE) content. However, cellulolytic bacteria addition up to 10% had no effect on crude protein (CP), extract ether (EE), dry matter (DM), organic matter (OM), glucose, and lactic acid content, as well as in vitro gas production. It could be concluded that cellulolytic bacteria addition in level 5% decreased CF content but did not give positive effect on in vitro gas production.